Flow Pattern in Hydrocyclones - Fernando Concha Arcil (KONA Powder and Particle Journal, 2014)
This paper presents a review of the flow pattern in hydrocyclones from a fluid dynamics perspective. Measurements attempt to establish the velocity and pressure distribution inside the equipment. With the experimental values of the velocity distributions, mass and linear momentum equations were solved using different approximations. The review starts with discussion of the principal experimental measurements in hydrocyclones and continues obtaining theoretical solutions to the equations with the simplest inviscid approach combining a free vortex with a sink, with rotational inviscid models, with models based on the exact solution of the Reynolds equation for highly idealized conditions and ends with solutions using different mathematical techniques such as asymptotic expansions, similarity solutions and boundary layer flows. When developments of the models can be found in the original papers they were not reproduced here, but in some cases they were include to relate them to a given fluid dynamic solution type.